Comorbidity and nutritional indices as predictors of morbidity after transurethral procedures: A prospective cohort study - Valerio, Massimo; Cerantola, Yannick; Fritschi, Urs; Hubner, Martin; Iglesias, Katia; Legris, Anne-Sophie; Lucca, Ilaria; Vlamopoulos, Yannis; Vaucher, Laurent; Jichlinski, Patrice (My University, 2014)
Introduction: Preoperative scores are widely used predictors of complications after major surgery. These scores, however, are not widely used in transurethral procedures. The aim of this study was to assess the value of the Charlson Comorbidity Index (CCI), the age-adjusted CCI, the American Society of Anesthesiologist score (ASA) and the Nutritional Risk Score (NRS) in predicting early morbidity after transurethral urological procedures.
Methods: Consecutive patients undergoing transurethral resection of the bladder or the prostate were prospectively enrolled. The scores were calculated preoperatively; 30-day complications were prospectively recorded according to the Dindo-Clavien classification. Univariate logistic regression was performed to investigate the value of each score and of other factors (i.e., age, sex, body mass index, anemia, smoking habit, type of operation and anaesthesia) as predictors of complications. A multivariate model was then calculated using these predictors.
Results: Overall, 197 patients were included. The mean age was 72 (standard deviation ± 10). In total, 26.9% patients had at least 1 complication. Using univariate analysis, we found that each score significantly predicted complications. In multivariate analysis, only the ASA (odds ration [OR] 2.11; 95% confidence interval [CI] 1.01-4.43) and the NRS (OR 2.42; 95% CI 1.56-3.74) remained independent predictors. The best model incorporated ASA, NRS and gender, and predicted morbidity with an area under the curve of 76%. Our study’s main limitations are population heterogeneity and limited sample size.
Conclusion: The ASA and the NRS are important and independent determinants of early morbidity after transurethral procedures. The use of these indices may assist clinicians in the decision-making process to balance the possible benefits of transurethral procedures with the potential risks.
Keywords: comorbidity; endoscopy; malnutrition; nutritional risk; postoperative complications